Arsenic exposure and serum antibody concentrations to diphtheria and tetanus toxoid in children at age 5: A prospective birth cohort in Bangladesh. (June 2019) - Welch, Barrett M.; Branscum, Adam; Ahmed, Sharia M.; Hystad, Perry; Smit, Ellen; Afroz, Sakila; Megowan, Meghan; Golam, Mostofa; Ibne Hasan, Md Omar Sharif; Rahman, Mohammad L.; Quamruzzaman, Quazi; Christiani, David C.; et al.
Abstract: Background: Arsenic can impair immune function. Timing of exposure can influence potential immunotoxicity of arsenic exposure. We examined the association between drinking water arsenic concentrations (W-As) measured repeatedly during different exposure windows in early life and serum concentrations of IgG antibodies against diphtheria and tetanus toxoids (diphtheria and tetanus antibody). Methods: A prospective cohort of pregnant women was recruited in Bangladesh (2008–2011). Averaged W-As levels were calculated for: pregnancy (W-Aspregnancy ): ≤16 weeks gestation and <1 month; toddlerhood (W-Astoddlerhood ): 12 and 20–40 months; and early childhood (W-Aschildhood ): 4–5 years. Serum was collected from 502 vaccinated children at age 5 and concentrations of diphtheria and tetanus toxoid IgG (i.e. antibody) were quantified. Antibody concentrations >0.1 IU/mL were considered clinically sufficient for protection. Associations were estimated using linear and logistic regression models. Results: Inverse associations were observed between W-Aspregnancy and serum diphtheria antibody levels, while null associations were observed between W-As and tetanus antibody. Children within the highest versus lowest tertile of W-Aspregnancy had 91% greater odds of having clinically insufficient concentrations of diphtheria antibody (Odds ratio:1.91, 95% confidence interval (CI): 1.03, 3.56). Among females, a doubling in W-Aspregnancy was associated with 12.3% (95%CI: −20.1%, −4.5%) lower median concentrations of diphtheria antibody. Tetanus antibody was only associated with W-Aspregnancy among females (percent change in median: −9.5%, 95%CI: −17.6%, −1.3%). Among children who were stunted or underweight, a doubling in W-Aspregnancy was associated with decreased diphtheria antibody of 19.8% (95%CI: −32%, −7.5%) and 14.3% (95%CI: −26.7%, −2%), respectively. Conclusions: Among vaccinated children, W-As measured during pregnancy was associated with decreased diphtheria antibody levels, but not tetanus antibody. However, W-As measured during toddlerhood and early childhood were not associated with either antibody outcome. Children's sex and malnutrition status were important effect modifiers of W-As for both diphtheria and tetanus antibody levels, highlighting the importance of these factors and the timing of the exposure when evaluating the effect of arsenic on humoral immunity. Highlights: Drinking water arsenic was negatively associated with vaccine-related diphtheria antibody. Null associations were observed between tetanus antibody titers and drinking water arsenic. Pregnancy appeared to be the most susceptible period for arsenic-related immunotoxicity. Arsenic-related effects were most pronounced in females, or children that were stunted growth or underweight.